Beauty and the beast: reading proposals in object-book format - Diana Maria Ferreira Martins; Sara Reis da Silva (Acta Scientiarum. Language and Culture, 2024)
The published offer aimed at children up to six years old has undergone exponential growth in recent decades, mainly those which give particular meaning to the materiality associated with the emotional and playful exploration of reading and contact with books as objects, frequently close to that of toys. We propose to analyze four object-books as part of this trend, often with a recreational and parodistic propensity dedicated to the rewriting or recovery of narratives constantly present in the oral tradition, in this concrete case arising from the short story Beauty and the beast popularized, in 1756, by Jeanne-Marie Leprince de Beaumont (1711–1780). The selected books, which are potentially addressed to pre-readers and early readers, show significant care in terms of editorial finishing, but also with regard to the markedly softened verbal-iconic recreation and, in certain cases, close to the universe of play for the instigations which they proposed. In these cases, the act of reading has a particular performative and experiential value, as we will endeavor to show.